FAST PYROLYSIS TEST WITH WHOLE SUGARCANE - CORTEZ, Luis A. B.; JORDAN, Rodrigo A.; PEREZ, Juan M. M.; BALDASSIN Jr, Ricardo; BARBIN, Douglas Fernandes (Revista Brasileira de Engenharia de Biossistemas, 2010)
This paper shows a preliminary study proposing the usage of whole sugarcane in the thermoconversion process. . Tests were made on fast pyrolysis of biomass as whole sugarcane (bagasse, sugar and sugarcane straw) crushed and dry. These experiments were performed in order to verify the suitability of this type of biomass for the fast pyrolysis process in a fluidized bed. The pre-treatment was assessed, during which, for the preparation of the whole sugarcane, an ordinary machine for chopping and grinding was employed. The pyrolysis process was conducted without major changes in the plant operating conditions to other biomass such as sugarcane trash. The efficiency of energy conversion of biomass to fine coal and bio-oil was 41%, resulting in a production of 3034 MJ per ton of the whole sugarcane processed, compared to 1900.6 MJ obtained in the production of ethanol via fermentation, where the conversion efficiency was around 26%. With the advances in this pyrolysis, efficiency may increase in the coming years, an interesting route for production of second generation fuels via catalytic synthesis using syngas from gasification of the mixture of bio-oil and fine charcoal.